2018
DOI: 10.1042/bsr20180458
|View full text |Cite
|
Sign up to set email alerts
|

Sorting machineries: how platelet-dense granules differ from α-granules

Abstract: Platelets respond to vascular injury via surface receptor stimulation and signaling events to trigger aggregation, procoagulant activation, and granule secretion during hemostasis, thrombosis, and vascular remodeling. Platelets contain three major types of secretory granules including dense granules (or δ-granules, DGs), α-granules (AGs), and lysosomes. The contents of platelet granules are specific. Platelet DGs store polyphosphate and small molecules such as ADP, ATP, Ca2+, and serotonin, while AGs package m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 78 publications
0
60
0
Order By: Relevance
“…It has been shown that larger platelets have denser αgranules, which store biologically active molecules such as GPIIb/IIIa, fibrinogen, and von Willebrand factor (vWf) which can initiate the coagulation cascade [30]. Dense granules store a variety of molecules which are secreted during platelet activation; including catecholamines, serotonin, calcium, adenosine 5′-diphosphate (ADP), and adenosine 5′-triphosphate (ATP) that involved in initiating coagulation cascade during inflammation [31]. Higher MPV is also seen with DIC and it has been shown that MPV plays an important role in activation of coagulation and/or hyperfibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that larger platelets have denser αgranules, which store biologically active molecules such as GPIIb/IIIa, fibrinogen, and von Willebrand factor (vWf) which can initiate the coagulation cascade [30]. Dense granules store a variety of molecules which are secreted during platelet activation; including catecholamines, serotonin, calcium, adenosine 5′-diphosphate (ADP), and adenosine 5′-triphosphate (ATP) that involved in initiating coagulation cascade during inflammation [31]. Higher MPV is also seen with DIC and it has been shown that MPV plays an important role in activation of coagulation and/or hyperfibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, platelets release various substances from their intracellular granules that contribute to coagulation . For example, plasma PPBP and PF4 reportedly activate coagulation .…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] In our splenic tissue analysis, hypothermia enhanced vWF expression in both mRNA and Upon activation, platelets release various substances from their intracellular granules that contribute to coagulation. [39][40][41][42][43][44] For example, plasma PPBP and PF4 reportedly activate coagulation. [45][46][47][48] Although we suspect that these substances were released into the plasma of hypothermic mice, we did not detect significant thrombosis or plasma D-dimer elevation in mice euthanized immediately after the hypothermia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dense granules have a distinct specific cargo regarding both biogenesis and function, which contains a few types of small molecules, such as catecholamines, ADP, ATP, polyphosphate and Ca 2+ [ 38 ].…”
Section: Platelet Biology and Its Roles In Human Diseasesmentioning
confidence: 99%